Comparative Analysis of Spectral Broadening Techniques for Optical Temperature Sensing in Yttrium Fluoride (YF3) Doped with Neodymium - Ruan P. R. Moura; Bárbara M. Cruz; Tatiane S. Lilge; Adriano B. Andrade; Mario E. G. Valerio; Zélia S. Macedo; José J. Rodrigues; Márcio A. R. C. Alencar (Sensors)
In this work, YF3:Nd3+ powder was synthesized using the microwave-assisted hydrothermal method at a low temperature (140 °C) and short synthesis time (1 h). The photoluminescence and optical temperature sensing properties of YF3:Nd3+ were examined using 800 nm laser excitation, focusing on the emission corresponding to the 4F3/2 → 4I9/2 transition of Nd3+. The performance of YF3:Nd3+ as an optical temperature sensor was evaluated using the full width at half maximum (FWHM), band broadening at 30% of maximum intensity (Δλ30%), and valley-to-peak intensity ratio (VPR) techniques. All techniques demonstrated good repeatability and reproducibility. The best results were obtained using the VPR (V1/P1) method, which exhibited the highest relative sensitivity and the lowest temperature uncertainty, with values of 0.69 ± 0.02% K−1 and 0.46 ± 0.09 K at 303 K, respectively. YF3:Nd3+ shows promise as an optical temperature sensor operating entirely within the first biological window.